Teisės ir etikos normų taikymas Lietuvos žurnalistų ir leidėjų etikos kodekse - Mažylė, Jolanta (Information & Media, 2009)
Straipsnyje apžvelgiama Lietuvos žiniasklaidos sistemos savitvarkos institucinė sąranga ir institucijų kompetencijos, mėginama nustatyti jų funkcinius aspektus. Taip pat aptariami bendrieji profesinių etikos kodeksų tikslai, reikalavimai tokių dokumentų turiniui ir formai. Šio straipsnio tikslas – atlikti Lietuvos žurnalistų ir leidėjų etikos kodekso kokybės turinio analizę, palyginti Visuomenės informavimo įstatyme ir Žurnalistų ir leidėjų etikos kodekse naudojamas normas ir nuostatas, užtikrinančias visuomenės informavimo rengėjų ir žurnalistų atsakingą ir skaidrią veiklą. Tyrimo metodas – apžvalginis, lyginamasis, apibendrinamasis.Pagrindiniai žodžiai: etika, teisė, funkcija, norma, įstatymas, profesinė etika, viešosios informacijos rengėjas, žiniasklaida, žurnalistas.Application of law and ethics rules in the Code of Ethics of Lithuanian journalists and publishersJolanta MažylėSummaryThis article presents a survery of the competence of the institutional system that regulates the provision of public information in Lithuania as well as ascertains the functional aspects of self-regulation institutions in the area of the provision of public information. Those factors are regulated by the Law on the Provision of Public Information. Three aspects of functional competencies of institutions – political, juridical and ethical are abstracted. The basic principles of professional ethical codes and requirements for the contents and form of such documents are also considered being important. The aim of the article is to analyse the quality of the content of Law on the Provision of Public Information and to compare its rules with the Code of Ethics of Lithuanian journalists and publishers. A detailed analysis of the content of the Code of Ethics of Lithuanian journalists and publishers leads to a conclusion that the content and form of this document setting down regulations on which journalists’ ethics in the area of public information is based, only partially covers the common principles of codes of professional ethics. A significant factor for making such conclusion is that the Code of Ethics of Lithuanian journalists and publishers is not a code intended for one professional group only.Although journalists, as well as organisers of public information, participate in the same field of the provision of information, there are differences in their juridical status. Investigation has revealed that a document regulating the professional ethics of two different groups in the area of the provision of public information does not involve the whole cohesive purposes as is recommended for such documents. This is caused by a factor that articles in the Code of Ethics of Lithuanian journalists and publishers often use the rules of law, and their basic content elements repeat the rules of laws in the same way as they are defined by the Law on the Provision of Public Information, Law on the Protection of Minors Against Detrimental Effect of Public Information, Law on Protection of Personal Information, Law of Authors’ rights, Law on Copyright and Related Rights.In this research paper, a comparative analysis of the Code of Ethics of Lithuanian journalists and publishers and the Law on the Provision of Public that 47 articles in the Law on the Provision of Public Information (out of 75) have the same essence as in the Code of Ethics of Lithuanian journalists and publishers. Three articles of the Code of Ethics of Lithuanian journalists and publishers have the duplicate formulation like the Law on the Provision of Public Information. However, transfer of legal rules from the Law on the Provision of Public Information into the code of professional ethics in such clichéd manner demonstrates low standards of juridical behaviour and juridical ignorance of the participants in the field of public communication, both organisers of public information and journalists. Evaluating the proportion of the rules of law, which are being used by the Code of Ethics of Lithuanian journalists and publishers, it is possible to propose that this Code is a set of legal rules, but not a document intended for a professional society to declare their principles and moral values.